Cybersecurity in the workplace: factors that influence positive cybersecurity behavior against phishing in South African institutions - Pilane, Karabo (Department of Information Systems, 2025)
In South Africa one of the top cybersecurity threats is phishing. Furthermore, employees' responses to phishing emails can either bolster or weaken an organisation's cyber security. It is estimated that more than 90% of data breaches are due to successful phishing attacks. They bring the maximum benefits with little to no cost for cyber attackers. Hence, this study aims to explain the factors that influence cybersecurity protective behaviour against phishing in South African organisations. A quantitative method was used, and data were collected online through a questionnaire survey. One hundred and twenty respondents from South African organisations participated. The partial least squares-structural equation modelling platform provided in SmartPLS-4 was used to model the data. SmartPLS was used to calculate and analyse reliability, convergent and discriminant validity, path coefficients, and significance of relationships. Factors that were identified as influencing cybersecurity protective behaviour against phishing were remote working, cybersecurity awareness, perceived user self-efficacy, facilitating conditions, perceived vulnerability, perceived severity, response efficacy, response costs, and government cyber laws enforcement.